IMPROVING THE STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH TEAM GAMES TOURNAMENT - DesiYusnanda Sari; Sri MindaMurni (Universitas Negeri Medan, 2014)
This study attempted to improve the students’ reading comprehension achievement in descriptive text through Team Games Tournament (TGT) method. This study was conducted by using classroom action research. The subject of the research was class IX SMP PAB 10 Medan Estate which consisted of 25 students. The research was conducted in two cycles and the first cycle consisted of four meetings the second cycle consisted of two meetings. The instruments for collecting the data were quantitative data (reading evaluation) and qualitative data (diary note, observation sheet and interview sheet). Based on reading scores, students’ score kept improving in every evaluation. In the test I the mean was 65,33, in the test II the mean was 71,72 and the test III the mean was 84,54.Based on diary note, observation sheet and interview sheet, it was found that teaching-learning process ran well. Students were active, enthusiastic, and interested in reading. The result of the research showed that Team Games Tournament (TGT) method significantly improved students’ achievement in reading comprehension especially in reading descriptive text.